Strategi Pengembangan Pemasaran Porang (Amorphophallus Muelleri Blume) di Kabupaten Sidenreng Rappang: Studi Kasus di PT Al-Fatih Porang Indonesia - Nur Aqidah; Iranita Haryono; Astrini Padapi (LP3M Universitas Putra Bangsa, 2025)
This research is a case study research. The aim of this research is to determine the marketing development strategy for porang. By using the SWOT Analysis technique. The method used in this research, namely the qualitative method, is a method that focuses on in-depth observation. And the types of data used are primary and secondary data. Results of research on PT Porang Marketing Development Strategy. Al-Fatih Porang Indonesia, Tallumae Village, Wattang Sidenreng District, Sidenreng Rappang Regency is an S-O (Strength-Opportunities) Strategy, namely taking advantage of existing profits and opportunities by: Easy to cultivate to increase production to meet market needs, Establishing collaboration with other agencies that then processed into several forms of products that have many benefits. Large areas of land can produce a lot of porang so they can meet market needs. Certified products are products that have been recognized internationally so that porang can grow in the market (market share). strength and weakness factor value) 2.65 and the Y value (difference in opportunity and threat factor values) 2.01 are used as the coordinate points for the internal and external factor analysis quadrants. So it is concluded that the coordinate points for the Porang Marketing Development Strategy at PT Al-Fatih Porang Indonesia Tallumae Village, Wattang Sidenreng District, Sidenreng Rappang District is in Quadrant I.